WORK SAMPLING METHOD FOR ANALYSIS OF PERFORMANCE AND DETERMINING THE NUMBER OF WORKERS IN THE WAREHOUSE DEPARTMENT - Sari, Sylvie Indah Kartika; Winata, Bintoro Dwi Krisna; Andriani, Debrina Puspita; Putro, Wisnu Wijayanto (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2021)
Industrial competition demands that each company be effective and efficient, hence companies need to make optimal use of resources. The purpose of this research is to determine the productivity of the workers in completing their work and to discover how much workload is caused by the activities carried out. In addition, recommendations for improvements were also given as an effort to reduce the high rate of overtime hours and determine the appropriate number of the workforce at spare parts and raw materials division. The results showed that some workforces have an uneven workload.